(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the new stage of trade and economic cooperation between Uzbekistan and Afghanistan, as well as the policies of the state leaders in the field of economics during this process. The purpose of the article is to highlight Uzbekistan’s contribution to the development of the neighboring Afghan economy, identify the areas of cooperation, and explore the future opportunities for these relations. Additionally, using international relations theory, the article compares the economic relations between the two countries, the areas of existing cooperation, and their potential for regional economic development. The research findings show that Uzbekistan is expanding its cooperation with Afghanistan in the areas of energy, transport and logistics, agriculture, and trade, thus contributing to the stability of the neighboring country’s economy. The study further demonstrates that trade and economic integration between Uzbekistan and Afghanistan not only strengthens bilateral relations but also improves the economic integration of the Central and South Asian regions. To further develop this cooperation in the future, it will be necessary to ensure political stability and implement additional investment projects.